(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article reviews the best practices of the United States in the use of adaptive sports as a tool for the rehabilitation and socialization of veterans with physical injuries. Adaptive sports play an important role in the rehabilitation process of military personnel, helping them restore health, set new goals, and maintain contact with the sports community. Competition, teamwork, and purposefulness motivate soldiers to move forward and achieve success. Participation in military adaptive sports allows recovered soldiers to once again feel the team spirit and test their strength in a competitive environment. The role of military organizations and government programs in supporting adaptive sports for veterans is extremely important in ensuring access to these opportunities. In the United States, there are several key initiatives aimed at supporting veterans through adaptive sports. Among them: Wounded Warrior Project (WWP); Invictus Games; VA Adaptive Sports Program; Warrior Games; The Paralympic Military Program; The National Veterans Wheelchair Games, and others. Veterans’ adaptive sports initiatives and programs in the United States have a major impact on their rehabilitation and socialization. They not only promote physical recovery, but also provide psychological support, social connections, and motivation to continue an active life after injury. These programs are often funded by both government agencies and through charitable organizations and corporate partners, allowing veterans to have access to the necessary resources and opportunities for rehabilitation. These programs play an important role in the rehabilitation and socialization of injured military personnel and veterans, using adaptive sports as a key element in the process of recovery and integration into society.